2020
DOI: 10.1111/jnc.15004
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin‐1 in the CNS: Emerging concepts in health and disease

Abstract: Pannexin‐1 (Panx1) is a large pore membrane channel with unique conduction properties ranging from non‐selective ion permeability to the extracellular release of signalling molecules. The release of ATP by Panx1 has been particularly well‐characterized with implications in purine signalling across a variety of biological contexts. Panx1 activity is also important in inflammasome formation and the secretion of pro‐inflammatory molecules such as interleukin‐1β. Within the central nervous system (CNS), Panx1 is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 171 publications
1
46
0
Order By: Relevance
“…A second and apparently independent role of metabotropic signaling in excitotoxicity involves pannexin channel opening. When activated, pannexin ion channels become permeable to Na + , Ca 2+ , and other ions and molecules (Yeung et al, 2020). Thompson and colleagues have shown that sustained NMDAr activation can induce pannexin-1 channel activation in the absence of ion flux through the NMDAr ion channel, with the resulting Ca 2+ and Na + influx essentially amplify the elevations caused by ion flux through the NMDAr itself.…”
Section: Non-ionotropic Nmdar Signaling In Excitotoxicitymentioning
confidence: 99%
“…A second and apparently independent role of metabotropic signaling in excitotoxicity involves pannexin channel opening. When activated, pannexin ion channels become permeable to Na + , Ca 2+ , and other ions and molecules (Yeung et al, 2020). Thompson and colleagues have shown that sustained NMDAr activation can induce pannexin-1 channel activation in the absence of ion flux through the NMDAr ion channel, with the resulting Ca 2+ and Na + influx essentially amplify the elevations caused by ion flux through the NMDAr itself.…”
Section: Non-ionotropic Nmdar Signaling In Excitotoxicitymentioning
confidence: 99%
“…3. Pannexin ion channels constitute 3 new members of the gap junction superfamily, first cloned from mammalian tissue 20 years ago (Barbe et al, 2006;Yeung et al, 2020). Panx1 is widely expressed on the plasma membrane of central neurons, glia, and endothelial cells.…”
Section: Other Cation Channelsmentioning
confidence: 99%
“…In addition, the pannexin (Panx) protein family could also perform Cx-hemichannel-like activity (Yeung et al, 2020). Panx usually does not form GJCs (Sosinsky et al, 2011;Sahu et al, 2014) and Panx channels have similar membrane topology and pharmacological properties to Cx hemichannels.…”
Section: Introductionmentioning
confidence: 99%
“…Panx usually does not form GJCs (Sosinsky et al, 2011;Sahu et al, 2014) and Panx channels have similar membrane topology and pharmacological properties to Cx hemichannels. However, Panx and Cx exhibit no significant sequence homology (Yeung et al, 2020). Panx1 and Panx2 expression have been found in neurons, however, their expression in astrocytes is still controversial, which may depend on the pathological condition (Vogt et al, 2005;Yeung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation